Maternal Depression and Associated Factors Among Pregnant Women Attending Ante Natal Care, Southern Ethiopia: Cross-Sectional Study - Borie, Yacob Abraham; Siyoum, Melese; Tsega, Aklile; Anbese, Gemechu (Frontiers in Public Health, 2022)
Background: Patients with depressed mental disorders may experience a lack of interest or pleasure, a poor mood, feelings of guilt or unworthiness, sleep and appetite disturbances, and easy fatigability. Based on the degree of the condition, depression is classed as mild, moderate, or severe. Maternal depression is the most common psychiatric condition during pregnancy, and its harmful effects have serious ramifications for both the mother and the fetus. Almost one in every four women will experience depression at some point in her life, the majority of which will occur during her childbearing years. Studies reports showed that antenatal depression is a common maternal problem in Ethiopia and as reported antenatal depression ranges in Ethiopia from 19.04 % to 29.92%. Objective: To assess the prevalence of maternal depression and associated factors among antenatal care attendants at Wolayta Sodo Teaching and Referral hospital, Southern Ethiopia. Methods: Health facility based cross-sectional study was conducted at Wolayta Sodo Teaching and Referral Hospital from May 01 to 30/2018. Data were collected from through face to face interview at exit from antenatal care unit using structured questionnaire and checklist adopted from patient Health Questionnaire (PHQ-9). Data were collected from 309 antenatal attendant mothers using systematic random sampling from each either mother. Binary and multivariable logistic regression model was employed to identify factors associated with maternal depression at P-value less than 0.05 level of significant. Result: Depression among pregnant mother was found to be 27.2 % (95% Cl: 22, 32%). Women’s level of education; being elementary school (AOR=6.35 95%CL (2.32, 17.38), completing high school and above (AOR=3.35, 95%CL 1.33, 8.47) were associated with maternal depression whereas having good husband support was protective for maternal depression (AOR=0.4, 95%CL: 0.19, 0.83) and also not using substance during pregnancy period was protective for maternal depression (AOR=0.39, 95%CI, 0.19, 0.77).Conclusion: The frequency of mother depression in this community was greater than in previous Ethiopian studies reported. Maternal depression was linked to a woman's level of education, husband support, and substance usage. Health care providers regarding pregnant women should emphasize the importance of husband support, substance usage and women level of education